Systemic inflammation enhances stimulant-induced striatal dopamine elevation - Petrulli, J R; Kalish, B; Nabulsi, N B; Huang, Y; Hannestad, J; Morris, E D (Translational psychiatry, 2017)
Changes in the mesolimbic dopamine (DA) system are implicated in a range of neuropsychiatric conditions including addiction, depression and schizophrenia. Dysfunction of the neuroimmune system is often comorbid with such conditions and affects similar areas of the brain. The goal of this study was to use positron emission tomography with the dopamine D 2 antagonist tracer, 11 C-raclopride, to explore the effect of acute immune activation on striatal DA levels. DA transmission was modulated by an oral methylphenidate (MP) challenge in order to reliably elicit DA elevation. Elevation in DA concentration due to MP was estimated via change in 11 C-raclopride binding potential from the baseline scan. Prior to the post-MP scan, subjects were pre-treated with either the immune activator lipopolysaccharide (LPS) or placebo (PBO) in a cross-over design. Immune activation was confirmed by measuring tumor necrosis factor alpha (TNFα), interleukin (IL)-6 and IL-8 concentration in plasma. Eight healthy subjects were scanned four times each to determine the MP-induced DA elevation under both LPS and PBO pre-treatment conditions. MP-induced DA elevation in the striatum was significantly greater ( P <0.01) after LPS pre-treatment compared to PBO pre-treatment. Seven of eight subjects responded similarly. This effect was observed in the caudate and putamen ( P <0.02), but was not present in ventral striatum. DA elevation induced by MP was significantly greater when subjects were pre-treated with LPS compared to PBO. The amplification of stimulant-induced DA signaling in the presence of systemic inflammation may have important implications for our understanding of addiction and other diseases of DA dysfunction.